Constitution Reposition of the 1945 Constitution in Justice Collaborators Based on Human Rights - Joko Cahyono; Herman Suryokumoro; Nurini Aprilianda; Setiawan Noerdajasakti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Arrangements for the implementation and granting of the status of collaborating witnesses or known as Justice Collaborator Which invites the issue of pros and cons about the benefits and consequences that can be used as legal commodities, as well as subjectivity in the provision of its determination. To answer the question that has become public unrest, a comprehensive interpretation of the law is needed both grammatically, historically and juridically in order to obtain an understanding of whether the legal politics in the LPSK Law which regulates the Justice Collaborator has been in accordance with the objectives in terms of uncovering the main actors and restoring state losses related to the economy and development. Furthermore, to examine why the determination of Justice Collaborator on corruption crimes does not immediately realize a social justice as in paragraph IV of the Preamble to the Republic of Indonesia Constitution Th. 1945. It is very possible that the existing norms are incomplete, so they must be reconstructed by accommodating the principles of expediency and justice while still having a progressive nature of law enforcement in order to create ideal norms.